A Patterned Graphene/ZnO UV Sensor Driven by Integrated Asymmetric Micro-Supercapacitors on a Liquid Metal Patterned Foldable Paper - Yun, Junyeong; Lim, Yein; Lee, Hanchan; Lee, Geumbee; Park, Heun; Hong, Soo Yeong; Jin, Sang Woo; Lee, Yong Hui; Lee, Sang-Soo; Ha, Jeong Sook (WILEY-V C H VERLAG GMBH, 2017)
A foldable array of patterned graphene/ZnO nanoparticle UV sensor and asymmetric micro-supercapacitors (AMSCs) integrated on a paper substrate with patterned liquid metal interconnections is reported. The resistor type UV sensor based on graphene/ZnO nanoparticles is patterned to be driven by the stored energy of the integrated AMSCs. The AMSC consists of MnO2 nanoball deposited multiwalled carbon nanotubes (MWNTs) and V2O5 wrapped MWNTs as positive and negative electrodes, respectively. As an electrolyte, propylene carbonate-poly(methyl methacrylate)-LiClO4, an organic solvent-based gel, is used. The UV sensor and AMSCs can be easily integrated on a liquid metal, Galinstan, patterned, waterproof mineral paper and show a mechanically stable UV sensing, regardless of repetitive folding cycles. This work demonstrates a novel foldable nanomaterial based sensor system driven by integrated energy storage devices, applicable to future wearable and portable electronics.
Keywords: THIN-FILM ELECTRODES; MANGANESE-DIOXIDE; FLEXIBLE SUPERCAPACITORS; POLYANILINE NANOFIBERS; COMPOSITE ELECTRODES; CARBON NANOTUBES; ENERGY-STORAGE; PERFORMANCE; OXIDE; ZNO